Human Capital Risk Factors on Workforce Sustainability Performance: an Organizational Behavior Perspective - Rahmat, Taufiq (KarismaPro, 2025)
This study aimed to analyze the impact of job insecurity and job stress as human capital risks on workforce sustainability performance. It is a descriptive study with a quantitative approach. Data were collected from industrial workers in Indonesia using a structured questionnaire. Structural Equation Modeling with the PLS technique was applied for analysis. The results showed that job insecurity had a stronger effect on turnover intention compared to job stress. The model explained 64.4% of the variance in turnover intention. The findings highlight the need for integrated human resource strategies to mitigate psychological threats that reduce workforce sustainability.